Benefits of Early Versus Delayed Palliative Care to Informal Family Caregivers of Patients With Advanced Cancer: Outcomes From the ENABLE III Randomized Controlled Trial - Dionne-Odom, J. Nicholas (J Clin Oncol, 2015)
PURPOSE: To determine the effect of early versus delayed initiation of a palliative care intervention for family caregivers (CGs) of patients with advanced cancer. PATIENTS AND METHODS: Between October 2010 and March 2013, CGs of patients with advanced cancer were randomly assigned to receive three structured weekly telephone coaching sessions, monthly follow-up, and a bereavement call either early after enrollment or 3 months later. CGs of patients with advanced cancer were recruited from a National Cancer Institute cancer center, a Veterans Administration Medical Center, and two community outreach clinics. Outcomes were quality of life (QOL), depression, and burden (objective, stress, and demand). RESULTS: A total of 122 CGs (early, n = 61; delayed, n = 61) of 207 patients participated; average age was 60 years, and most were female (78.7%) and white (92.6%). Between-group differences in depression scores from enrollment to 3 months (before delayed group started intervention) favored the early group (mean difference, −3.4; SE, 1.5; d = −.32; P = .02). There were no differences in QOL (mean difference, −2; SE, 2.3; d = −.13; P = .39) or burden (objective: mean difference, 0.3; SE, .7; d = .09; P = .64; stress: mean difference, −.5; SE, .5; d = −.2; P = .29; demand: mean difference, 0; SE, .7; d = −.01; P = .97). In decedents' CGs, a terminal decline analysis indicated between-group differences favoring the early group for depression (mean difference, −3.8; SE, 1.5; d = −.39; P = .02) and stress burden (mean difference, −1.1; SE, .4; d = −.44; P = .01) but not for QOL (mean difference, −4.9; SE, 2.6; d = −.3; P = .07), objective burden (mean difference, −.6; SE, .6; d = −.18; P = .27), or demand burden (mean difference, −.7; SE, .6; d = −.23; P = .22). CONCLUSION: Early-group CGs had lower depression scores at 3 months and lower depression and stress burden in the terminal decline analysis. Palliative care for CGs should be initiated as early as possible to maximize benefits.